2012
DOI: 10.1007/s10456-012-9321-x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration- and schedule-dependent effects of chemotherapy on the angiogenic potential and drug sensitivity of vascular endothelial cells

Abstract: The anti-angiogenic activity of chemotherapy is both dose- and schedule-dependent. While conventional maximum tolerated dose (MTD) chemotherapy exerts only mild and reversible anti-angiogenic effects, low-dose metronomic (LDM) chemotherapy was developed to specifically target tumour angiogenesis. However, the long-term effects of either MTD or LDM chemotherapy on vascular endothelial cells have never been investigated. Here, we demonstrated that repeated exposure to MTD and LDM chemotherapy differentially impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 43 publications
(63 reference statements)
3
33
0
1
Order By: Relevance
“…29 Indeed, it has been suggested that the repeated exposure to low-dose metronomic treatment with oral E might impair the angiogenic potential of endothelial cells and increase their chemosensitivity. 30 These preclinical data might further support the rationale for the current study in which, indeed, the combination of the antiangiogenic agent Bev with low-dose metronomic oral E was used as maintenance treatment after induction chemotherapy in patients with ED-SCLC who responded to treatment. We acknowledge that our findings, even if promising, are derived from a small single-institution experience.…”
Section: Discussionsupporting
confidence: 52%
“…29 Indeed, it has been suggested that the repeated exposure to low-dose metronomic treatment with oral E might impair the angiogenic potential of endothelial cells and increase their chemosensitivity. 30 These preclinical data might further support the rationale for the current study in which, indeed, the combination of the antiangiogenic agent Bev with low-dose metronomic oral E was used as maintenance treatment after induction chemotherapy in patients with ED-SCLC who responded to treatment. We acknowledge that our findings, even if promising, are derived from a small single-institution experience.…”
Section: Discussionsupporting
confidence: 52%
“…The antiangiogenic effect of metronomic chemotherapy on the tumor vasculature may be mediated via increased levels of the endogenous angiogenesis inhibitor thrombospondin-1 (TSP-1) (6). TSP-1 is produced not only by stromal cells, but also by cancer cells (7), and induces apoptosis in circulating endothelial cells (8)(9)(10)(11). Other negative regulators of angiogenesis (e.g., endostatin, soluble VEGF receptors) also can affect vascular function (6).…”
mentioning
confidence: 99%
“…Chemotherapy hampers the infl ammatory response, reducing oxygen delivery to the wound and increasing the likelihood of infection [15]. Lawrence et al, found that these delays in wound healing were especially pronounced in cases where chemotherapeutic agents were administered pre-operatively or within 3 weeks post-operatively [7].…”
Section: Discussionmentioning
confidence: 99%